Implementasi Alat Permainan Edukatif (APE) untuk Menstimulasi Motorik Halus Anak Usia Dini di Kelurahan Srengseng, Jakarta Barat - Bimo Kuncoro Jati; Riswano Riswano; Rachmadina Rafika Triani; Candra Karismawan (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
This community service program aims to enhance fine motor skills in early childhood through the utilization of Educational Play Tools (EPT) at PAUD/RA Al Istiqomah, Kembangan District, West Jakarta. The program employed a community-based participatory approach involving 25 children aged 4–6 years, along with teachers and parents. The method consisted of five stages: needs assessment, preparation, intervention implementation, evaluation, and program sustainability. Data were collected using participatory observation with a checklist instrument covering hand-eye coordination, grip strength, object manipulation accuracy, and attention span. The results indicate improvements across all fine motor skill indicators, with the highest increase observed in object manipulation accuracy. In addition, qualitative reflections revealed that teachers and parents gained better understanding and skills in providing developmental stimulation through play-based activities. The collaborative approach between school and family played a significant role in supporting program sustainability. However, these findings should be interpreted cautiously due to the short duration of the intervention and the limited number of participants. Further studies with more rigorous designs are recommended. Overall, the use of educational play tools through play-based learning demonstrates potential as a practical and contextually relevant strategy to support fine motor development in early childhood education settings.